Physiological and skeletal muscle responses to high-intensity interval exercise in Thoroughbred horses - Mukai, Kazutaka; Ohmura, Hajime; Takahashi, Yuji; Ebisuda, Yusaku; Yoneda, Koki; Miyata, Hirofumi (Frontiers in Veterinary Science, 2023)
The purpose of this study was to determine whether acute high-intensity interval exercise or sprint interval exercise induces greater physiological and skeletal muscle responses compared to moderate-intensity continuous exercise in horses. Methods: In a randomized crossover design, eight trained Thoroughbred horses performed three treadmill exercise protocols consisting of moderate-intensity continuous exercise (6 min at 70% VO2max; MICT), high-intensity interval exercise (6 × 30 s at 100% VO2max; HIIT), and sprint interval exercise (6 × 15 s at 120% VO2max; SIT). Arterial blood samples were collected to measure blood gas variables and plasma lactate concentration. Biopsy samples were obtained from the gluteus medius muscle before, immediately after, 4 h, and 24 h after exercise for biochemical analysis, western blotting and real-time RT-PCR. Effects of time and exercise protocol were analyzed using mixed models (P<0.05). Results: Heart rate and plasma lactate concentration at the end of exercise were higher in HIIT and SIT than those in MICT (heart rate, HIIT vs. MICT, P=0.0005; SIT vs. MICT, P=0.0015; lactate, HIIT vs. MICT, P=0.0014; SIT vs. MICT, P=0.0003). Arterial O2 saturation and arterial pH in HIIT and SIT were lower compared with MICT (SaO2, HIIT vs. MICT, P=0.0035; SIT vs. MICT, P=0.0265; pH, HIIT vs. MICT, P=0.0011; SIT vs. MICT, P=0.0023). Muscle glycogen content decreased significantly in HIIT (P=0.0004) and SIT (P=0.0016) immediately after exercise, but not in MICT (P=0.19). Phosphorylation of AMP-activated protein kinase (AMPK) in HIIT showed a significant increase immediately after exercise (P=0.014), but the increase was not significant in MICT (P=0.13) and SIT (P=0.39). At 4 h after exercise, peroxisome proliferator-activated receptor γ co-activator-1α mRNA increased in HIIT (P=0.0027) and SIT (P=0.0019) and vascular endothelial growth factor mRNA increased in SIT (P=0.0002). Discussion: Despite an equal run distance, HIIT and SIT cause more severe arterial hypoxemia and lactic acidosis compared with MICT. In addition, HIIT activates the AMPK signaling cascade, and HIIT and SIT elevate mitochondrial biogenesis and angiogenesis, whereas MICT did not induce any significant changes to these signaling pathways.